Analisi Manajemen Club Banjarbaru Archery school - Talita, Nourma; Warni, Herita; Rakhman, Arie (Universitas Hamzanwadi, 2024)
This research aims to examine the sports coaching management of club banjarbaru archery school. The method used was descriptive qualitative research. The population is all management in club banjarbaru archery school. The sample was selected purposive sampling with 1 club owner, 3 coaches, and 6 athletes. Data collection utilizes more than one technique, namely observation, interviews, and documentation. The data analysis used is descriptive analysis. The results in this study are in the observation of research finding good management of club banjarbaru archery school, the results of interviews researchers determine the management of club banjarabarub archery school, and the documentation that researchers get in this research to support the answers from the acquisition of observations and interviews. The conclusion in this study shows the management of club banjarabaru archery school in the fields of management, coaches, athletes, facilities and infrastructure contained in club banjarbaru archery school, and organizing is still in the developing stage.